2021
DOI: 10.1016/j.cgh.2020.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Burden of Nonalcoholic Steatohepatitis

Abstract: BACKGROUND & AIMS:Nonalcoholic steatohepatitis (NASH) is associated with an increase in healthcare resource use and poor health-related quality of life (HRQoL). We assessed the humanistic and economic burden of NASH, disease management, and patient journey. METHODS:We performed a cross-sectional analysis of data, collected from July through November 2017, from the Growth from Knowledge Disease Atlas Real-World Evidence program, reported by physicians in United States, France, and Germany. We extracted demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…On the other hand, Golabi et al reported that HRQoL scores were the lowest for HCV patients, followed by NAFLD patients. These differences may be attributed to the use of different HRQoL scoring indices (domain scores of the 29-item Chronic Liver Disease Questionnaire (CLDQ) in Dan’s study versus the NHANES HRQOL-4 questionnaire in Golabi’s study) [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Golabi et al reported that HRQoL scores were the lowest for HCV patients, followed by NAFLD patients. These differences may be attributed to the use of different HRQoL scoring indices (domain scores of the 29-item Chronic Liver Disease Questionnaire (CLDQ) in Dan’s study versus the NHANES HRQOL-4 questionnaire in Golabi’s study) [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the quality of life and stresses of patients with MAFLD are still lacking, since most studies on MAFLD have focused on its pathophysiology and management. Further, existing studies on correlation with quality of life used the traditional NAFLD criteria [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…All five studies scored highly in all or most relevant quality assessment categories (see section 3.4 for further details). Studies indicate a high demand for pharmacological and non-pharmacological interventions, as well as diagnosis and monitoring tests (Table 3) [22,27,29,30]. Use of tests and procedures varied depending on disease severity, as shown by one multinational study that showed increased utilisation of non-invasive tests and procedures in patients with more advanced fibrosis (stage 4 [F4]) [29].…”
Section: Healthcare Resource Utilisationmentioning
confidence: 99%
“… 11 Other symptoms include abdominal bloating/swelling, abdominal discomfort, sleep disturbance, or apnea. 12 There are no data on difference in presentations amongst various ethnicities.…”
Section: Diagnosis and Manifestationsmentioning
confidence: 99%